Polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption, preparation method and application of polarized bismuth titanate / PPy positive electrode material in lithium-sulfur battery
By using polarized bismuth titanate/PPy positive electrode material that enhances polysulfide adsorption on the positive electrode of the lithium sulfur battery, the problem of "shuttle effect" caused by poor sulfur conductivity in lithium sulfur batteries is solved, and the cycle stability and discharge specific capacity of the battery are significantly improved.
Patent Information
- Application Number
- CN202411973240.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The active substance of lithium-sulfur batteries has poor conductivity, resulting in a "shuttle effect" during the charge and discharge cycle, which makes its charge and discharge capacity too low and destroys the cycle stability of the battery.
Polarized bismuth titanate/PPy positive electrode material that enhances polysulfide adsorption, which enhances the polarization electric field of bismuth titanate through polarization treatment, polymerizes the conductive polymer PPy in situ on its surface, and finally deposits nano-level sulfur particles by thiamine chemical method.
It significantly improves the conductivity of the sulfur positive electrode, suppresses the "shuttle effect", and improves the discharge specific capacity and cycle stability of lithium-sulfur batteries.
Smart Images

Figure CN119786563A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy storage application and secondary battery electrode material preparation, and specifically relates to a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption, a preparation method and application thereof in lithium-sulfur batteries. Background Art
[0002] With the rapid development of smart devices, electric vehicles, and low-cost and high-efficiency energy storage systems, people have put forward higher requirements on the energy density, cycle life, and safety performance of energy storage batteries. Lithium-sulfur batteries (Li-S) have a high theoretical specific capacity (1675 mAh g -1 ) and theoretical energy density (2600 Wh kg -1 ) is considered to be an ideal new generation of secondary batteries. As the main active material of the positive electrode of lithium-sulfur batteries, elemental sulfur has broad application prospects due to its abundant raw materials, low price, and environmental friendliness.
[0003] However, the active sulfur and discharge product lithium sulfide of lithium-sulfur batteries have poor conductivity. During the charge and discharge cycle, the long-chain lithium polysulfide of the intermediate product will diffuse to the lithium negative electrode for electrodeposition, resulting in a "shuttle effect", which makes its charge and discharge capacity too low, destroys the cycle stability of the battery, and inevitably reduces its performance, which seriously hinders its commercial application. Therefore, it is necessary to find a host material that can inhibit the "shuttle effect" and combine it with sulfur to improve the electrochemical performance of lithium-sulfur batteries. Summary of the invention
[0004] In view of the problem in the prior art that when elemental sulfur is used as the positive electrode of a lithium-sulfur battery, the shuttle effect is serious, the conductivity is poor, and the discharge specific capacity is low, resulting in poor cycle performance, the purpose of the present invention is to provide a polarized bismuth titanate / PPy positive electrode material and a preparation method for enhancing polysulfide adsorption, and its application in lithium-sulfur batteries. The polarized bismuth titanate / PPy positive electrode material has a strong adsorption capacity for polysulfides and can significantly improve the conductivity of the sulfur positive electrode, effectively inhibit the shuttle effect during the charge and discharge process, thereby improving the discharge specific capacity and cycle stability of the sulfur positive electrode.
[0005] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps: The bismuth titanate nanosheets are polarized to obtain polarized bismuth titanate nanosheets; Adding a pyrrole dispersion and an oxidant to a water dispersion of polarized bismuth titanate nanosheets to carry out polymerization reaction to obtain a polarized bismuth titanate / PPy composite material; Sulfur nanoparticles were deposited on the surface of bismuth titanate / PPy composite material by thiamine chemistry to obtain polarized bismuth titanate / PPy cathode material with enhanced polysulfide adsorption.
[0006] Furthermore, before the bismuth titanate nanosheets are subjected to polarization treatment, the bismuth titanate nanosheets are subjected to tablet pressing treatment; the pressure of the tablet pressing treatment is 5-20 MPa; The voltage of the polarization treatment is 0.1-20 kV, and the polarization time is 10-60 min; the polarization treatment method is corona polarization or oil bath polarization.
[0007] Furthermore, the thickness of the bismuth titanate nanosheets is 20~80 nm; The oxidant is one or both of ferric chloride and ammonium persulfate.
[0008] Furthermore, sulfur nanoparticles are deposited on the surface of the bismuth titanate / PPy composite material by a thiamine chemical method to obtain a polarized bismuth titanate / PPy positive electrode material with enhanced polysulfide adsorption, comprising the following steps: The sulfur-ethylenediamine solution was added to the water and ethanol dispersion of the polarized bismuth titanate / PPy composite material, the pH value was adjusted to 7.0, filtered, and dried.
[0009] The dosage ratio of polarized bismuth titanate nanosheets, pyrrole and oxidant is 0.01 g~1 g:0.1 mL~10 mL:0.01 g~0.1 g; Furthermore, the polymerization reaction temperature is 0°C and the time is 1 to 10 h.
[0010] Furthermore, the volume ratio of water to ethanol is 1:1~10:1, the mass ratio of sulfur to ethylenediamine is 1:20~40, and the dosage ratio of polarized bismuth titanate / PPy composite material, water and sulfur is 0.1 g~1 g:100 mL~1000 mL:0.3 g~3 g.
[0011] Furthermore, bismuth titanate nanosheets are prepared by the following process: adding a molten salt medium to a dispersion containing a bismuth source and a titanium source, ball milling, and drying to obtain a precursor powder; The precursor powder is ground and sintered to obtain bismuth titanate nanosheets.
[0012] Furthermore, the bismuth source is Bi2O4, and the titanium source is TiO2; The molten salt medium is one or more of NaCl, KCl, KF and BaCl2; The ball milling time is 1-12 h, and the rotation speed is 200-600 r / min; The sintering temperature is 700-1000°C, the heating rate is 1-10°C / min, and the sintering time is 1-6 h.
[0013] A polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption, wherein the particle size of sulfur loaded on the polarized bismuth titanate / PPy positive electrode material is 5 nm to 10 nm.
[0014] A lithium-sulfur battery comprises a positive electrode and a negative electrode, wherein the positive electrode is made of a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption, wherein the bismuth titanate nanosheet is first polarized, and then a layer of conductive polymer PPy is polymerized on the surface of the nanosheet by in-situ polymerization, and finally sulfur nanoparticles are deposited on the surface of the ultra-thin bismuth titanate / PPy composite material by a thiamine chemical method, and the composite material is used as a positive electrode of a lithium-sulfur battery. The bismuth titanate nanosheet has a large specific surface area and can provide more reactive sites. The polarization electric field of bismuth titanate is adjusted by polarization treatment, and lithium polysulfide, an intermediate product of the lithium-sulfur battery, is effectively adsorbed. The in-situ polymerized PPy greatly improves the conductivity of the composite material, thereby inhibiting the dissolution of polysulfide compounds in the electrolyte, effectively reducing the "shuttle effect", and thus improving the electrochemical cycle stability of the lithium-sulfur battery.
[0016] Furthermore, the bismuth titanate nanosheets are polarized by applying an external electric field to change the dipole orientation of the bismuth titanate nanosheets and the polarity of the bismuth titanate itself, thereby enhancing the adsorption of lithium polysulfide, an intermediate of lithium-sulfur batteries, and inhibiting the shuttle effect of lithium polysulfide.
[0017] Furthermore, the voltage of the polarization treatment is 0.1~20 kV. The appropriate electric field can induce a strong electric dipole moment, significantly enhance the material's adsorption capacity for polysulfides, and inhibit the diffusion of polysulfides through polar interactions; if the electric field is too small, the polarization of the material is insufficient, and it is difficult to effectively enhance the adsorption capacity; if the electric field is too large, it may lead to the destruction of the material structure or the non-uniformity of the electron migration path, which is not conducive to performance optimization.
[0018] Furthermore, the polarization time is 10-60 min. The polarization time needs to be long enough to form a stable electric dipole moment, but too long may cause side reactions or excessive energy consumption. Too short a polarization time may lead to insufficient polarization, and the surface charge distribution of the material is not fully optimized, affecting the adsorption and catalytic ability; too long a polarization time may cause deformation of the internal lattice of the ferroelectric material and accumulation of residual stress. This stress may cause local damage to the crystal structure and reduce the adsorption and catalytic performance of lithium polysulfide. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a scanning electron microscope image of the polarized bismuth titanate / PPy / S ultra-thin sheet composite material in Example 1.
[0020] Figure 2 This is the X-ray diffraction image of the polarized bismuth titanate / PPy ultra-thin sheet composite material in Example 1.
[0021] Figure 3 This is a diagram of polysulfide adsorption of the polarized bismuth titanate / PPy ultra-thin sheet composite material assembled into a lithium-sulfur battery in Example 1.
[0022] Figure 4 The rate performance of the lithium-sulfur battery assembled from the polarized bismuth titanate / PPy / S ultra-thin sheet composite material in Example 1. DETAILED DESCRIPTION
[0023] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0024] Ferroelectric materials have attracted much attention due to their unique physical properties such as ferroelectricity, piezoelectricity, and ferroelasticity, which have promoted their wide application in the fields of electronics, energy, and environment. The wonderful ferroelectric "spontaneous polarization" caused by this asymmetric crystal structure provides new opportunities for catalytic applications. Considering that polysulfides are also polar, the polarity of ferroelectric materials is enhanced by polarization to enhance the capture strategy of polysulfides to solve the shuttle effect. However, bismuth titanate itself has poor conductivity, so the conductivity of the material can be improved by in-situ polymerization of conductive polymers, thereby achieving the effect of complementing each other's strengths.
[0025] The present invention discloses a method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption. First, a molten salt method is used to prepare bismuth titanate ultra-thin nanosheets. Then, a polarization device is used to polarize the bismuth titanate ultra-thin nanosheets. Then, a layer of ultra-thin conductive polymer PPy is in situ polymerized on the surface of the polarized bismuth titanate ultra-thin nanosheets. Finally, sulfur nanoparticles with a size of 5 nm to 10 nm are deposited on the surface of the polarized bismuth titanate / PPy ultra-thin nanosheets by a thiamine chemical method. Through polarization treatment, the polarization electric field inside the bismuth titanate is enhanced, which can effectively adsorb polysulfides; through in-situ polymerization of PPy, the conductivity of the composite material can be improved, thereby improving the discharge capacity and sulfur utilization rate of the lithium-sulfur battery; finally, the nano-scale sulfur particles prepared by the thiamine chemical method are helpful to improve the sulfur discharge capacity. Specifically, the following steps are included: S1. Disperse the bismuth source and the titanium source in anhydrous ethanol.
[0026] S2. Add the molten salt medium into the solution in step S1, place it in a ball mill, and perform ball milling and drying.
[0027] S3, grinding and sintering the precursor powder obtained in step S2, and naturally cooling to room temperature after sintering.
[0028] S4, washing the powder obtained in step S3, filtering it by vacuum filtration, centrifugation or freeze drying, and drying it to obtain bismuth titanate (Bi4Ti3O 12 ) ultrathin nanosheets.
[0029] S5, pressing the bismuth titanate ultra-thin nanosheets obtained in step S4, and then polarizing the bismuth titanate discs by applying voltage.
[0030] S6, ultrasonically dispersing the polarized bismuth titanate ultrathin nanosheets obtained in step S5 into deionized water, then adding the pyrrole dispersion, and finally adding the oxidant, and performing a polymerization reaction under stirring in a cold water bath (0°C) for 1 to 10 hours to obtain a powder. Pyrrole, as a conductive polymer monomer, plays a conductive role.
[0031] S7. Wash the powder obtained in step S6, filter it by vacuum filtration, centrifugation, freeze drying, etc., and dry it to obtain a polarized bismuth titanate / PPy composite material.
[0032] S8, dispersing the polarized bismuth titanate / PPy composite material obtained in step S7 in a mixed solution of water and ethanol, then dissolving sulfur powder in an ethylenediamine solution to form a sulfur-ethylenediamine solution, finally adding the sulfur-ethylenediamine solution drop by drop into the solution dispersed with the polarized bismuth titanate / PPy composite material, finally adding an acid solution dropwise into the mixed solution until the pH value of the mixed solution reaches 7.0, filtering, washing, and drying to obtain a polarized bismuth titanate / PPy / S ultra-thin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm to 10 nm.
[0033] The bismuth source described in step 1 is Bi2O4, and the titanium source is TiO2.
[0034] The molten salt medium described in step 2 includes one or more of NaCl, KCl, KF and BaCl2; The ball milling time described in step 2 is 1 to 12 h, and the rotation speed is 200 to 600 r / min.
[0035] The sintering temperature described in step 3 is 700~1000°C, the heating rate is 1~10°C / min, and the sintering time is 1~6 h.
[0036] The pressure of the tableting process in step 5 is 5~20 MPa.
[0037] The voltage of the polarization treatment in step 5 is 0.1-20 kV, and the polarization time is 10-60 min; the polarization treatment method is corona polarization or oil bath polarization.
[0038] The oxidant in step 6 is one or more of ferric chloride and ammonium persulfate.
[0039] The mass ratio of polarized bismuth titanate ultrathin nanosheets, pyrrole and oxidant in step 6 is 0.01 g~1 g:0.1 mL~10 mL:0.01 g~0.1 g.
[0040] The volume ratio of water to ethanol in step 8 is 1:1~10:1; the mass ratio of sulfur powder to ethylenediamine is 1:20~40, the dropping speed of sulfur-ethylenediamine solution is 1~10 mL / min, the acid solution includes one or more of hydrochloric acid (mass concentration of 10-20%), sulfuric acid (mass concentration of 10-20%), nitric acid (mass concentration of 10-20%) and acetic acid; the amount ratio of polarized bismuth titanate / PPy composite material, water and sulfur is 0.1 g~1 g:100 mL~1000 mL:0.3 g~3 g.
[0041] A polarized bismuth titanate / PPy positive electrode material with enhanced polysulfide adsorption prepared by the above method.
[0042] The technical scheme of the present invention is further described in detail below through examples, but the present invention is not limited in any way.
[0043] Example 1 A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps; According to Bi4Ti3O 12 According to the stoichiometric ratio, 10 mmol of titanium dioxide and 15 mmol of bismuth oxide were weighed and dispersed in 30 mL of anhydrous ethanol, and then 10 g of sodium chloride was added, and the mixture was placed in a ball mill for ball milling for 4 h at a speed of 400 r / min. The ball milled powder was dried for 12 h and then ground for 1 h to obtain a precursor powder. The precursor powder was placed in a nitrogen atmosphere (gas flow rate of 50 mL / min), and then heated to 800 °C at a rate of 2 °C / min, sintered for 4 h, and naturally cooled to room temperature after sintering. The obtained powder was washed, vacuum filtered, and dried to obtain bismuth titanate ultra-thin nanosheets with a thickness of 50 nm. 0.2 g of bismuth titanate ultrathin nanosheets were placed in a powder tablet press at a pressure of 10 MPa to form discs; the bismuth titanate discs were placed in a corona polarization device at a voltage of 10 kV and a polarization time of 30 min to obtain polarized bismuth titanate ultrathin nanosheets, the polarized bismuth titanate ultrathin nanosheets were dispersed in 300 mL of aqueous solution, 1 mL of pyrrole was added to the aqueous solution, and 0.05 g of ferric chloride was added after stirring evenly, and the polymerization reaction was carried out under stirring in a cold water bath (0°C) for 3 h, and the obtained powder was washed, vacuum filtered, and dried to obtain the polarized bismuth titanate / PPy composite material; 0.2 g of polarized bismuth titanate / PPy composite material was dispersed in a mixed solution of water and ethanol, the volume ratio of water to ethanol was 10:1, and the amount of water was 200 mL. Sulfur powder was dissolved in ethylenediamine solution to form a sulfur-ethylenediamine solution, the mass ratio of sulfur powder to ethylenediamine was 1:25, and the amount of sulfur powder was 0.6 g. The sulfur-ethylenediamine solution was added dropwise at a dropping rate of 1 mL / min. Finally, hydrochloric acid with a mass concentration of 10% was added dropwise until the pH value of the mixed solution was 7.0. The mixture was filtered, washed, and dried to obtain a polarized bismuth titanate / PPy / S ultrathin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm~10 nm.
[0044] Finally, the polarized bismuth titanate / PPy / S ultra-thin sheet composite material was mixed with a conductive carbon material and a binder in a mass ratio of 70:20:10 as the positive electrode, and metallic lithium was used as the negative electrode to assemble a button battery.
[0045] See also Figure 1It can be seen that the polarized bismuth titanate / PPy / S ultra-thin sheet composite material presents a two-dimensional ultra-thin sheet morphology, the size of the nanosheets ranges from 0.5μm to 2 μm, and is evenly dispersed. The ultra-thin nanosheet structure has a high specific surface area and two-dimensional structural characteristics, which can provide more active sites, fully contact with sulfur and polysulfides, and improve the utilization rate of sulfur. Reduce the bulk density of sulfur, improve the dispersibility of sulfur, and alleviate volume expansion.
[0046] See also Figure 2 It can be seen that through the XRD test analysis, all the characteristic peaks of the polarized bismuth titanate / PPy positive electrode material prepared in this embodiment can correspond to the standard PDF card, and no other impurity peaks are found, indicating that the prepared polarized bismuth titanate / PPy positive electrode material has high purity and good crystallinity.
[0047] See also Figure 3 , the polarized bismuth titanate / PPy prepared in Example 1 was added to a 5mmol / L Li2S6 solution. The first one in the figure was polarized without voltage, and the following five were polarized at 0.1kV, 5 kV, 10 kV, 15 kV, and 20 kV, respectively. It can be seen that with the increase of polarization voltage, the adsorption capacity of bismuth titanate / PPy positive electrode material for Li2S6 gradually increased, resulting in a decrease in the polysulfide concentration in the solution, and finally causing the solution color to become lighter. This phenomenon reflects the key role of polarized bismuth titanate / PPy in adsorbing polysulfides and regulating the chemical conversion of polysulfides.
[0048] The battery performance was tested on the Wuhan Blue Electric CT2001A battery test system. The current density is calculated in C, 1C=1675mAhg-1, and all tests were performed at 25°C. The battery was charged and discharged by constant current, that is, a constant current was given to the battery, and the curve of the current change over time of the battery under long-term discharge state was studied in the voltage window of 1.7 V~2.8 V. The test results can be found in Figure 4 .
[0049] See also Figure 4 , Figure 4 The black portion in the figure is pure S / CB (composite material of sulfur / conductive carbonization), i.e., the positive electrode material is not prepared by the method of the invention. It can be seen that the discharge specific capacities of the polarized bismuth titanate / PPy / S electrode at 0.1C, 0.2C, 0.5C, 1C, 2C, and 4C are 1190, 925.7, 794.2, 639.3, 490.3, and 337.9 mAh g -1, which is much higher than 670, 562.1, 477.1, 400.5, 325, and 159.5 of the conventional conductive carbon black / sublimated sulfur electrode in the comparative example. Moreover, the polarized bismuth titanate / PPy / S electrode still has a discharge capacity of 835.1 mAh g when the discharge rate finally returns to 0.1C. -1 The reversible discharge capacity is very high. Since the bismuth titanate ultra-thin nanosheets have a large specific surface area, they can provide more active reaction sites. The polarization electric field of bismuth titanate is adjusted by polarization treatment, which effectively adsorbs lithium polysulfide, the intermediate product of lithium-sulfur batteries. The in-situ polymerized PPy greatly improves the conductivity of the composite material, thereby inhibiting the dissolution of polysulfide compounds in the electrolyte and effectively reducing the "shuttle effect", thereby significantly improving the electrochemical cycle stability of lithium-sulfur batteries.
[0050] Example 2 A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps; According to Bi4Ti3O 12 According to the stoichiometric ratio, 20 mmol of titanium dioxide and 30 mmol of bismuth oxide were weighed and dispersed in 30 mL of anhydrous ethanol, and then 10 g of sodium chloride and 10 g of potassium chloride were added, and the mixture was placed in a ball mill for ball milling for 6 h at a speed of 300 r / min. The ball milled powder was dried for 12 h and then ground for 1 h to obtain a precursor powder. The precursor powder was placed in a nitrogen atmosphere (gas flow rate of 50 mL / min), and then heated to 700 °C at a rate of 3 °C / min, sintered for 5 h, and naturally cooled to room temperature after sintering. The obtained powder was washed, vacuum filtered, and dried to obtain 60 nm thick bismuth titanate ultrathin nanosheets. 0.2 g of bismuth titanate ultrathin nanosheets were placed in a powder tablet press at a pressure of 15 MPa to form discs; the bismuth titanate discs were placed in a corona polarization device at a voltage of 15 kV and a polarization time of 30 min to obtain polarized bismuth titanate ultrathin nanosheets, the polarized bismuth titanate ultrathin nanosheets were dispersed in 300 mL of aqueous solution, 2 mL of pyrrole was added to the aqueous solution, and 0.05 g of ferric chloride was added after stirring, and the polymerization reaction was carried out under stirring in a cold water bath (0°C) for 6 h, and the obtained powder was washed, vacuum filtered, and dried to obtain a polarized bismuth titanate / PPy composite material; 0.1 g of polarized bismuth titanate / PPy composite material was dispersed in a mixed solution of water and ethanol, the volume ratio of water to ethanol was 10:1, and the amount of water was 250 mL. Sulfur powder was dissolved in ethylenediamine solution to form a sulfur-ethylenediamine solution, the mass ratio of sulfur powder to ethylenediamine was 1:25, and the amount of sulfur powder was 0.3 g. The sulfur-ethylenediamine solution was added dropwise at a dropping rate of 2 mL / min. Finally, hydrochloric acid with a mass concentration of 20% was added dropwise until the pH value of the mixed solution was 7.0. The mixture was filtered, washed, and dried to obtain a polarized bismuth titanate / PPy / S ultrathin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm~10 nm.
[0051] Finally, the polarized bismuth titanate / PPy / S ultra-thin sheet composite material and the binder were mixed in a mass ratio of 70:20:10 as the positive electrode, and metallic lithium was used as the negative electrode to assemble a button battery.
[0052] Example 3 A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps; According to Bi4Ti3O 12 According to the stoichiometric ratio, 300 mmol of titanium dioxide and 45 mmol of bismuth oxide were weighed and dispersed in 30 mL of anhydrous ethanol, and then 15 g of sodium chloride and 15 g of barium chloride were added, and the mixture was placed in a ball mill for ball milling for 6 h at a speed of 300 r / min. The ball milled powder was dried for 12 h, and then ground for 1 h to obtain a precursor powder. The precursor powder was placed in a nitrogen atmosphere (gas flow rate of 50 mL / min), and then heated to 900 °C at a rate of 4 °C / min, sintered for 3 h, and naturally cooled to room temperature after sintering. The obtained powder was washed, vacuum filtered, and dried to obtain 60 nm thick bismuth titanate ultrathin nanosheets. 0.2 g of bismuth titanate ultrathin nanosheets were placed in a powder tablet press at a pressure of 15 MPa to form discs; the bismuth titanate discs were placed in a corona polarization device at a voltage of 5 kV and a polarization time of 30 min to obtain polarized bismuth titanate ultrathin nanosheets, the polarized bismuth titanate ultrathin nanosheets were dispersed in 300 mL of aqueous solution, 1 mL of pyrrole was added to the aqueous solution, and after stirring evenly, 0.05 g of ammonium persulfate was added, and the polymerization reaction was carried out under stirring in a cold water bath (0°C) for 2 h, and the obtained powder was washed, vacuum filtered, and dried to obtain the polarized bismuth titanate / PPy composite material; 0.3 g of polarized bismuth titanate / PPy composite material was dispersed in a mixed solution of water and ethanol, the volume ratio of water to ethanol was 10:1, and the amount of water was 350 mL. Sulfur powder was dissolved in ethylenediamine solution to form a sulfur-ethylenediamine solution, the mass ratio of sulfur powder to ethylenediamine was 1:26, and the amount of sulfur powder was 1 g. The sulfur-ethylenediamine solution was added dropwise at a dropping rate of 3 mL / min. Finally, hydrochloric acid with a mass concentration of 15% was added dropwise until the pH value of the mixed solution was 7.0. The mixture was filtered, washed, and dried to obtain a polarized bismuth titanate / PPy / S ultrathin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm~10 nm.
[0053] Finally, the polarized bismuth titanate / PPy / S ultra-thin sheet composite material and the binder were mixed in a mass ratio of 70:20:10 as the positive electrode, and metallic lithium was used as the negative electrode to assemble a button battery.
[0054] Example 4 A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps; According to Bi4Ti3O 12 According to the stoichiometric ratio, 10 mmol of titanium dioxide and 15 mmol of bismuth oxide were weighed and dispersed in 30 mL of anhydrous ethanol, and then 5 g of sodium chloride was added, and the mixture was placed in a ball mill for ball milling for 4 h at a speed of 600 r / min. The ball milled powder was dried for 12 h, and then ground for 1 h to obtain a precursor powder. The precursor powder was placed in a nitrogen atmosphere (gas flow rate of 50 mL / min), and then heated to 1000 °C at a rate of 5 °C / min, sintered for 4 h, and naturally cooled to room temperature after sintering. The obtained powder was washed, vacuum filtered, and dried to obtain bismuth titanate ultrathin nanosheets with a thickness of 45 nm. 0.2 g of bismuth titanate ultrathin nanosheets were placed in a powder tablet press at a pressure of 20 MPa to form discs; the bismuth titanate discs were placed in a corona polarization device at a voltage of 15 kV and a polarization time of 20 min to obtain polarized bismuth titanate ultrathin nanosheets, the polarized bismuth titanate ultrathin nanosheets were dispersed in 300 mL of aqueous solution, 1 mL of pyrrole was added to the aqueous solution, and 0.05 g of ferric chloride was added after stirring, and the polymerization reaction was carried out under stirring in a cold water bath (0°C) for 7 h, and the obtained powder was washed, vacuum filtered, and dried to obtain the polarized bismuth titanate / PPy composite material; 0.2 g of polarized bismuth titanate / PPy composite material was dispersed in a mixed solution of water and ethanol, the volume ratio of water to ethanol was 5:1, and the amount of water was 300 mL. Sulfur powder was dissolved in ethylenediamine solution to form a sulfur-ethylenediamine solution, the mass ratio of sulfur powder to ethylenediamine was 1:24, and the amount of sulfur powder was 0.6 g. The sulfur-ethylenediamine solution was added dropwise at a dropping rate of 1 mL / min. Finally, sulfuric acid with a mass concentration of 12% was added dropwise until the pH value of the mixed solution was 7.0. The mixture was filtered, washed, and dried to obtain a polarized bismuth titanate / PPy / S ultrathin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm~10 nm.
[0055] Finally, the polarized bismuth titanate / PPy / S ultra-thin sheet composite material and the binder were mixed in a mass ratio of 70:20:10 as the positive electrode, and metallic lithium was used as the negative electrode to assemble a button battery.
[0056] Example 5 A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps; According to Bi4Ti3O 12 According to the stoichiometric ratio, 10 mmol of titanium dioxide and 15 mmol of bismuth oxide were weighed and dispersed in 30 mL of anhydrous ethanol, and then 5 g of potassium chloride was added, and the mixture was placed in a ball mill for ball milling for 8 h at a speed of 500 r / min. The ball milled powder was dried for 12 h, and then ground for 1 h to obtain a precursor powder. The precursor powder was placed in a nitrogen atmosphere (gas flow rate of 50 mL / min), and then heated to 1000 °C at a rate of 5 °C / min, sintered for 3 h, and naturally cooled to room temperature after sintering. The obtained powder was washed, vacuum filtered, and dried to obtain bismuth titanate ultrathin nanosheets with a thickness of 70 nm. 0.2 g of bismuth titanate ultrathin nanosheets were placed in a powder tablet press at a pressure of 15 MPa to form discs; the bismuth titanate discs were placed in an oil bath polarization device at a voltage of 10 kV and a polarization time of 30 min to obtain polarized bismuth titanate ultrathin nanosheets, the polarized bismuth titanate ultrathin nanosheets were dispersed in 300 mL of aqueous solution, 1 mL of pyrrole was added to the aqueous solution, and 0.08 g of ferric chloride was added after stirring, and the polymerization reaction was carried out under stirring in a cold water bath (0°C) for 10 h, and the obtained powder was washed, vacuum filtered, and dried to obtain the polarized bismuth titanate / PPy composite material; 0.2 g of polarized bismuth titanate / PPy composite material was dispersed in a mixed solution of water and ethanol, the volume ratio of water to ethanol was 8:1, and the amount of water was 450 mL. Sulfur powder was dissolved in ethylenediamine solution to form a sulfur-ethylenediamine solution, the mass ratio of sulfur powder to ethylenediamine was 1:32, and the amount of sulfur powder was 0.75 g. The sulfur-ethylenediamine solution was added dropwise at a dropping rate of 1 mL / min. Finally, nitric acid with a mass concentration of 18% was added dropwise until the pH value of the mixed solution was 7.0. The mixture was filtered, washed, and dried to obtain a polarized bismuth titanate / PPy / S ultrathin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm~10 nm.
[0057] Finally, the polarized bismuth titanate / PPy / S ultra-thin sheet composite material and the binder were mixed in a mass ratio of 70:20:10 as the positive electrode, and metallic lithium was used as the negative electrode to assemble a button battery.
[0058] Example 6 A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps; According to Bi4Ti3O 12 According to the stoichiometric ratio, 20 mmol of titanium dioxide and 30 mmol of bismuth oxide were weighed and dispersed in 30 mL of anhydrous ethanol, and then 10 g of sodium chloride and 10 g of barium chloride were added, and the mixture was placed in a ball mill for ball milling for 12 h at a speed of 400 r / min. The ball milled powder was dried for 12 h and then ground for 1 h to obtain a precursor powder. The precursor powder was placed in a nitrogen atmosphere (gas flow rate of 50 mL / min), and then heated to 950 °C at a rate of 2 °C / min, sintered for 4 h, and naturally cooled to room temperature after sintering. The obtained powder was washed, vacuum filtered, and dried to obtain 65 nm thick bismuth titanate ultrathin nanosheets. 0.1 g of bismuth titanate ultrathin nanosheets were placed in a powder tablet press at a pressure of 15 MPa to form discs; the bismuth titanate discs were placed in an oil bath polarization device at a voltage of 10 kV and a polarization time of 60 min to obtain polarized bismuth titanate ultrathin nanosheets, the polarized bismuth titanate ultrathin nanosheets were dispersed in 300 mL of aqueous solution, 0.05 mL of pyrrole was added to the aqueous solution, and 0.02 g of ammonium persulfate was added after stirring, and the polymerization reaction was carried out under stirring in a cold water bath (0°C) for 1 h, and the obtained powder was washed, vacuum filtered, and dried to obtain the polarized bismuth titanate / PPy composite material; 0.4 g of polarized bismuth titanate / PPy composite material was dispersed in a mixed solution of water and ethanol, the volume ratio of water to ethanol was 8:1, and the amount of water was 400 mL. Sulfur powder was dissolved in ethylenediamine solution to form a sulfur-ethylenediamine solution, the mass ratio of sulfur powder to ethylenediamine was 1:35, and the amount of sulfur powder was 1.2 g. The sulfur-ethylenediamine solution was added dropwise at a dropping rate of 1 mL / min. Finally, hydrochloric acid with a mass concentration of 15% was added dropwise until the pH value of the mixed solution was 7.0. The mixture was filtered, washed, and dried to obtain a polarized bismuth titanate / PPy / S ultrathin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm~10 nm. Finally, the polarized bismuth titanate / PPy / S ultra-thin sheet composite material and the binder were mixed in a mass ratio of 70:20:10 as the positive electrode, and metallic lithium was used as the negative electrode to assemble a button battery.
[0059] Example 7 A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps; According to Bi4Ti3O 12 According to the stoichiometric ratio, 30 mmol of titanium dioxide and 45 mmol of bismuth oxide were weighed and dispersed in 30 mL of anhydrous ethanol, and then 10 g of sodium chloride, 10 g of barium chloride and 10 g of potassium chloride were added, and the mixture was placed in a ball mill for ball milling for 2 h at a speed of 500 r / min. The ball milled powder was dried for 12 h and then ground for 1 h to obtain a precursor powder. The precursor powder was placed in a nitrogen atmosphere (gas flow rate of 50 mL / min), and then heated to 900 °C at a rate of 4 °C / min, sintered for 5 h, and naturally cooled to room temperature after sintering. The obtained powder was washed, vacuum filtered and dried to obtain bismuth titanate ultra-thin nanosheets with a thickness of 54 nm. 0.3 g of bismuth titanate ultrathin nanosheets were placed in a powder tablet press at a pressure of 20 MPa to form discs; the bismuth titanate discs were placed in an oil bath polarization device, the voltage was set to 10 kV, and the polarization time was 40 min to obtain polarized bismuth titanate ultrathin nanosheets, the polarized bismuth titanate ultrathin nanosheets were dispersed in 300 mL of aqueous solution, 3 mL of pyrrole was added to the aqueous solution, and 0.06 g of ferric chloride was added after stirring, and the polymerization reaction was carried out under stirring in a cold water bath (0°C) for 9 h, and the obtained powder was washed, vacuum filtered, and dried to obtain the polarized bismuth titanate / PPy composite material; 0.2 g of polarized bismuth titanate / PPy composite material was dispersed in a mixed solution of water and ethanol, the volume ratio of water to ethanol was 4:1, and the amount of water was 300 mL. Sulfur powder was dissolved in ethylenediamine solution to form a sulfur-ethylenediamine solution, the mass ratio of sulfur powder to ethylenediamine was 1:30, and the amount of sulfur powder was 0.45 g. The sulfur-ethylenediamine solution was added dropwise at a rate of 2 mL / min. Finally, hydrochloric acid with a mass concentration of 10% was added dropwise until the pH value of the mixed solution was 7.0. The mixture was filtered, washed, and dried to obtain a polarized bismuth titanate / PPy / S ultrathin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm to 10 nm. Finally, the polarized bismuth titanate / PPy / S ultra-thin sheet composite material and the binder were mixed in a mass ratio of 70:20:10 as the positive electrode, and metallic lithium was used as the negative electrode to assemble a button battery.
[0060] Example 8 A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps; According to Bi4Ti3O 12 According to the stoichiometric ratio, 20 mmol of titanium dioxide and 30 mmol of bismuth oxide were weighed, dispersed in 30 mL of anhydrous ethanol, and then 15 g of sodium chloride was added, and the mixture was placed in a ball mill for ball milling for 10 h at a speed of 400 r / min. The ball milled powder was dried for 12 h, and then ground for 1 h to obtain a precursor powder. The precursor powder was placed in a nitrogen atmosphere (gas flow rate of 50 mL / min), and then heated to 750 °C at a rate of 2 °C / min, sintered for 6 h, and naturally cooled to room temperature after sintering. The obtained powder was washed, vacuum filtered, and dried to obtain bismuth titanate ultrathin nanosheets with a thickness of 45 nm. 0.1 g of bismuth titanate ultrathin nanosheets were placed in a powder tablet press at a pressure of 5 MPa to form a disc; the bismuth titanate disc was placed in an oil bath polarization device at a voltage of 5 kV and a polarization time of 60 min to obtain a polarized bismuth titanate ultrathin nanosheet, the polarized bismuth titanate ultrathin nanosheet was dispersed in 300 mL of aqueous solution, 1 mL of pyrrole was added to the aqueous solution, and 0.1 g of ferric chloride was added after stirring, and the polymerization reaction was carried out under stirring in a cold water bath (0°C) for 7 h, and the obtained powder was washed, vacuum filtered, and dried to obtain a polarized bismuth titanate / PPy composite material; 0.2 g of polarized bismuth titanate / PPy composite material was dispersed in a mixed solution of water and ethanol, the volume ratio of water to ethanol was 9:1, and the amount of water was 300 mL. Sulfur powder was dissolved in ethylenediamine solution to form a sulfur-ethylenediamine solution, the mass ratio of sulfur powder to ethylenediamine was 1:25, and the amount of sulfur powder was 0.8 g. The sulfur-ethylenediamine solution was added dropwise at a rate of 2 mL / min. Finally, hydrochloric acid with a mass concentration of 20% was added dropwise until the pH value of the mixed solution was 7.0. The mixture was filtered, washed, and dried to obtain a polarized bismuth titanate / PPy / S ultrathin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm to 10 nm. Finally, the polarized bismuth titanate / PPy / S ultra-thin sheet composite material and the binder were mixed in a mass ratio of 70:20:10 as the positive electrode, and metallic lithium was used as the negative electrode to assemble a button battery.
[0061] Example 9 A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps; According to Bi4Ti3O 12 According to the stoichiometric ratio, 10 mmol of titanium dioxide and 15 mmol of bismuth oxide were weighed and dispersed in 30 mL of anhydrous ethanol, and then 10 g of potassium fluoride was added, and the mixture was placed in a ball mill for ball milling. The ball milling time was 1 h and the rotation speed was 200 r / min. The ball-milled powder was dried for 12 h and then ground for 1 h to obtain a precursor powder. The precursor powder was placed in a nitrogen atmosphere (gas flow rate was 50 mL / min), and then heated to 850 °C at a rate of 1 °C / min, sintered for 3 h, and naturally cooled to room temperature after sintering. The obtained powder was washed, vacuum filtered, and dried to obtain bismuth titanate ultrathin nanosheets with a thickness of 20 nm. 0.01 g of bismuth titanate ultrathin nanosheets were placed in a powder tablet press at a pressure of 12 MPa to form discs; the bismuth titanate discs were placed in a corona polarization device at a voltage of 0.1 kV and a polarization time of 10 min to obtain polarized bismuth titanate ultrathin nanosheets, the polarized bismuth titanate ultrathin nanosheets were dispersed in 300 mL of aqueous solution, 0.1 mL of pyrrole was added to the aqueous solution, and after stirring evenly, 0.05 g of ferric chloride and 0.05 g of ammonium persulfate were added, and the polymerization reaction was carried out under stirring in a cold water bath (0°C) for 1 h, and the obtained powder was washed, vacuum filtered, and dried to obtain the polarized bismuth titanate / PPy composite material; 0.2 g of polarized bismuth titanate / PPy composite material was dispersed in a mixed solution of water and ethanol, the volume ratio of water to ethanol was 1:1, and the amount of water was 500 mL. Sulfur powder was dissolved in ethylenediamine solution to form a sulfur-ethylenediamine solution, the mass ratio of sulfur powder to ethylenediamine was 1:20, and the amount of sulfur powder was 1.1 g. The sulfur-ethylenediamine solution was added dropwise at a dropping rate of 5 mL / min. Finally, hydrochloric acid with a mass concentration of 10% was added dropwise until the pH value of the mixed solution was 7.0. The mixture was filtered, washed, and dried to obtain a polarized bismuth titanate / PPy / S ultrathin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm~10 nm.
[0062] Example 10 A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption comprises the following steps; According to Bi4Ti3O 12 According to the stoichiometric ratio, 10 mmol of titanium dioxide and 15 mmol of bismuth oxide were weighed and dispersed in 30 mL of anhydrous ethanol, and then 10 g of sodium chloride was added, and the mixture was placed in a ball mill for ball milling. The ball milling time was 5 h and the rotation speed was 350 r / min. The ball-milled powder was dried for 12 h and then ground for 1 h to obtain a precursor powder. The precursor powder was placed in a nitrogen atmosphere (gas flow rate was 50 mL / min), and then heated to 1000 °C at a rate of 10 °C / min, sintered for 1 h, and naturally cooled to room temperature after sintering. The obtained powder was washed, vacuum filtered, and dried to obtain bismuth titanate ultra-thin nanosheets with a thickness of 80 nm. 0.2 g of bismuth titanate ultrathin nanosheets were placed in a powder tablet press at a pressure of 17 MPa to form discs; the bismuth titanate discs were placed in a corona polarization device at a voltage of 20 kV and a polarization time of 50 min to obtain polarized bismuth titanate ultrathin nanosheets, the polarized bismuth titanate ultrathin nanosheets were dispersed in 300 mL of aqueous solution, 10 mL of pyrrole was added to the aqueous solution, and 0.1 g of ferric chloride was added after stirring, and the polymerization reaction was carried out under stirring in a cold water bath (0°C) for 10 h, and the obtained powder was washed, vacuum filtered, and dried to obtain the polarized bismuth titanate / PPy composite material; 1 g of polarized bismuth titanate / PPy composite material was dispersed in a mixed solution of water and ethanol, the volume ratio of water to ethanol was 3:1, and the amount of water was 1000 mL. Sulfur powder was dissolved in ethylenediamine solution to form a sulfur-ethylenediamine solution, the mass ratio of sulfur powder to ethylenediamine was 1:40, and the amount of sulfur powder was 3 g. The sulfur-ethylenediamine solution was added dropwise at a dropping rate of 10 mL / min. Finally, hydrochloric acid with a mass concentration of 10% was added dropwise until the pH value of the mixed solution reached 7.0. The mixture was filtered, washed, and dried to obtain a polarized bismuth titanate / PPy / S ultrathin sheet composite material loaded with sulfur nanoparticles with a size of 5 nm~10 nm.
[0063] The rate performance of the lithium-sulfur battery assembled from the polarized bismuth titanate / PPy / S ultra-thin sheet composite materials in Examples 1 to 10 is shown in Table 1.
[0064] Table 1 Comparison of rate performance of lithium-sulfur batteries assembled from polarized bismuth titanate / PPy / S ultra-thin sheet composite materials in Examples 1 to 10
[0065] The purpose of the polymerization reaction in the present invention is: since sulfur and bismuth titanate themselves have poor conductivity, a layer of ultra-thin conductive polymer PPy can be in situ polymerized on the surface of polarized bismuth titanate nanosheets to effectively improve the conductivity of the composite material, thereby reducing the charge transfer resistance during the charging and discharging process.
[0066] In the present invention, sulfur-ethylenediamine solution is added to the water and ethanol dispersion of the polarized bismuth titanate / PPy composite material, and sulfur particles are loaded by the thiamine method. The purpose is: the sulfur particles prepared by the thiamine method are nanoparticles, and the nanosulfur particles can form a closer contact with the conductive matrix to enhance the electron transmission capacity; they also have a higher specific surface area, can provide more reactive sites, and accelerate the reaction kinetics of sulfur and lithium, overcoming the problem that the commercial sublimated sulfur particle size is generally tens of microns, and the intrinsic conductivity of sulfur is extremely poor, and the sublimated sulfur of large particles further aggravates this problem. Larger particles lead to a smaller contact area between sulfur and the conductive material, which limits the electron transmission capacity and leads to a problem of reduced electrochemical reaction activity.
[0067] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0068] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption, characterized in that: The following steps are involved: The bismuth titanate nanosheets are polarized to obtain polarized bismuth titanate nanosheets; Adding a pyrrole dispersion and an oxidant to a water dispersion of polarized bismuth titanate nanosheets to carry out polymerization reaction to obtain a polarized bismuth titanate / PPy composite material; Sulfur nanoparticles were deposited on the surface of bismuth titanate / PPy composite material by thiamine chemistry to obtain polarized bismuth titanate / PPy cathode material with enhanced polysulfide adsorption.
2. The method for preparing the polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption according to claim 1, characterized in that: Before the bismuth titanate nanosheets are subjected to polarization treatment, the bismuth titanate nanosheets are subjected to tabletting treatment; the pressure of the tabletting treatment is 5-20 MPa; The voltage of the polarization treatment is 0.1-20 kV, and the polarization time is 10-60 min; the polarization treatment method is corona polarization or oil bath polarization.
3. The method for preparing the polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption according to claim 1, characterized in that: The thickness of bismuth titanate nanosheets is 20-80 nm; The oxidant is one or both of ferric chloride and ammonium persulfate.
4. The method for preparing the polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption according to claim 1, characterized in that: The method uses a thiamine chemical method to deposit sulfur nanoparticles on the surface of a bismuth titanate / PPy composite material to obtain a polarized bismuth titanate / PPy positive electrode material with enhanced polysulfide adsorption, comprising the following steps: The sulfur-ethylenediamine solution was added to the water and ethanol dispersion of the polarized bismuth titanate / PPy composite material, the pH value was adjusted to 7.0, filtered, and dried.
5. The method for preparing the polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption according to claim 4, characterized in that: The dosage ratio of polarized bismuth titanate nanosheets, pyrrole and oxidant is 0.01 g~1 g:0.1 mL~10 mL:0.01 g~0.1 g; The polymerization temperature is 0°C and the time is 1~10 h.
6. The method for preparing the polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption according to claim 4, characterized in that: The volume ratio of water to ethanol is 1:1~10:1, the mass ratio of sulfur to ethylenediamine is 1:20~40, and the dosage ratio of polarized bismuth titanate / PPy composite material, water and sulfur is 0.1 g~1 g:100 mL~1000 mL:0.3 g~3 g.
7. The method for preparing the polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption according to claim 1, characterized in that: Bismuth titanate nanosheets are prepared by the following process: adding a molten salt medium to a dispersion containing a bismuth source and a titanium source, ball milling, and drying to obtain a precursor powder; The precursor powder is ground and sintered to obtain bismuth titanate nanosheets.
8. The method for preparing the polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption according to claim 7, characterized in that: The bismuth source is Bi2O4, and the titanium source is TiO2; The molten salt medium is one or more of NaCl, KCl, KF and BaCl2; The ball milling time is 1-12 h, and the rotation speed is 200-600 r / min; The sintering temperature is 700-1000°C, the heating rate is 1-10°C / min, and the sintering time is 1-6 h.
9. A polarized bismuth titanate / PPy positive electrode material with enhanced polysulfide adsorption prepared by the method according to any one of claims 1 to 8, characterized in that: The particle size of sulfur loaded on the polarized bismuth titanate / PPy positive electrode material is 5 nm to 10 nm.
10. A lithium-sulfur battery, characterized in that: It comprises a positive electrode and a negative electrode, wherein the positive electrode is made of a polarized bismuth titanate / PPy positive electrode material for enhancing polysulfide adsorption prepared by the method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Lithium sulfur battery composite cathode material and preparation method thereof
CN108054350A
Preparation method for composite material based on Bi4Ti3O12@C / S, composite material and application
CN110416512A
Bismuth ferrite@titanium dioxide composite material for lithium-sulfur battery diaphragm and preparation method
CN110911623A
Sulfur-containing composite material as well as preparation method and application thereof
CN111009651A
Composite material, preparation method and application of composite material
CN111082002A